The association of gender and education field factors with the employment pattern of degree alumni: a case study of a Malaysian public university / Hanitahaiza Hairuddin ... [et al.] - Hairuddin, Hanitahaiza; Md Ab Malik, Ariff; Chuah, Soo-Cheng; Abdullah, Nabilah; Mohamad, Norhasnida; Abdul Hamid, Nurzeatul Hamimah; Abdul-Rahman, Shuzlina (Universiti Teknologi Mara Selangor, 2024)
Job employability is one of the leading indicators in evaluating the effectiveness of a university’s educational strategies to offer quality academic programs and meet job market expectations. In the context of a Malaysian Public University (MPU), job employability is critical in ensuring the government’s aspiration of achieving positive productivity, good market growth, and an increase in community involvement through structurally sound employment of graduates. As such, this study is carried out to investigate the job employability trend among alumni. Analysis was carried out on the undergraduate degree data of 13,512 respondents from 2006 to 2018 by extracting them from the Malaysian Ministry of Higher Education’s university tracer study system (SKPG2). Several hypotheses were developed and tested using the Chi-Square test and Cross-tabulation technique using SPSS 22.0. All the tested hypotheses produced significant results. Several comparisons of two situations, namely during the convocation and the SKPG2 exercise, show the occurrence of a job transition trend among alumni from private jobs and owned businesses to government jobs. Also, the average salary received by these respondents was mostly below RM3,000, which falls into the B2 group of Malaysia’s B40 household income category. It is concerning that there has been a significant decline in alumni business participation after graduation, indicating the need for fresh activities to realize the university's goal. It is hoped that this research will assist university administrators in reviewing and reframing their approaches to pursuing institutional goals.